Effects of fiscal instability on financial instability - Sundoo Hwang (KDI Journal of Economic Policy, 2022)
This paper empirically examines how fiscal instability affects financial instability. According to an IMF forecast (2021a), the fiscal space in Korea will be steadily reduced in the future. The theoretical literature predicts that if fiscal stability is undermined, financial stability will also be in danger given that government guarantees on banks are weakened and/or sovereign bonds held in banks become riskier. This paper empirically finds the existence of this negative impact of fiscal instability on financial instability. I also find that the intensity of this fiscal-financial relationship is greater in a country where (i) its currency is not a reserve currency such as the US dollar or euro, (ii) its banking sector is large relative to government sector, and/or (iii) its private credit to GDP is high. Korea has all of these three characteristics and hence needs to put more effort into maintaining fiscal stability.
Keywords: G01; G21; H60; 330; Fiscal Instability; Financial Instability; Sovereign Bond; Implicit Government Guarantees; Noncore Currency